Exploring "high tech" and "high touch" interaction capabilities: aligning the IT portfolio with customer and supplier relationships. Issue 2 (18th May 2020) - Ekman, Peter; Dahlin, Peter; Erixon, Cecilia; Thompson, Steven
Abstract : Purpose: To explore the emergent characteristics of IT portfolios in business-to-business (B2B) firms. The goal is to develop a model that clarifies what interaction capabilities B2B firms develop and to what form of IT this corresponds to. Design/methodology/approach: We apply an a priori conceptual framework that is based on the Industrial Marketing and Purchasing (IMP) Group's theoretical focus on business relationships. The framework depicts the business relationship as dealing with uncertainty and equivocality as well as building and upholding reliance and trust. We utilize a case study approach involving a focal firm and ten of its customers and suppliers. Building on 60 interviews, field observations and archival data, we analyze interviewee responses and the complementary data to evaluate the role of IT in supporting or automated various aspects of organizational relationships. Findings: Results show how "high tech" and "high touch" relate to different interaction capabilities, which firms develop based on the characteristics of their business relationships. Although IT is associated with "high tech" and "high touch" interaction capabilities, some forms of IT are deployed to support the former, while other forms support the later. Both forms of technology-enabled interaction capabilities require investment, and firms must balance investment costs against the value created by improved interaction capabilities. Originality/value: Our findings emphasize the interorganizational perspective (dyadic or network) rather than a solely organizational perspective for understanding IT portfolio development. This perspective is presented through an emergent tech–touch interaction capability model that shows how B2B firms can align their IT portfolio based on the specific characteristics of their business relationships.